An experimental study on the influence of input parameters on bend allowance in bending of sheet metal - Nguyễn , Thanh Tân; Trần , Thế San; Nguyễn , Thị Hồng Minh (Journal of Technical Education Science, 2013)
In this paper, we present the results from influences of the part geometry to flat pattern for AA5052-H32, based on these results we wrote a program to calculate flat pattern dimensions and bending locations which make accurate and efficient preparation for manufacturing process